Operational efficiency of Islami Bank Bangladesh Limited and comparison with other fully shariah based Islami Banks in Bangladesh - Hanif, Sheikh Abu (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.